2011
DOI: 10.1111/j.1742-4658.2011.08289.x
|View full text |Cite
|
Sign up to set email alerts
|

Hatching enzyme of Japanese eel Anguilla japonica and the possible evolution of the egg envelope digestion mechanism

Abstract: We purified eel hatching enzyme (EHE) from the hatching liquid of Japanese eel Anguilla japonica belonging to Elopomorpha to a single band on SDS ⁄ PAGE. TOF-MS analysis revealed that the purified EHE contained several isozymes with similar molecular masses. Comparison of the egg envelope digestion specificities of the purified EHE and of recombinant EHE4, one of the EHE isozymes, suggested that the isozymes contained in the purified EHE were functionally the same in terms of egg envelope digestion. By electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…The specific caseinolytic activities of the nickel column-purified rMfHE1 and rMfHE3 were 26.8 and 14.2 Δ 280  · min −1  · mg protein −1 , respectively. These values are similar to those of other fish hatching enzymes (30.7 Δ 280  · min −1  · mg protein −1 for ZHE1, 27.3 Δ 280  · min −1  · mg protein −1 for MHCE, and 18.4 Δ 280  · min −1  · mg protein −1 for MLCE) [19]. Thus, we concluded that recombinant enzymes were of sufficient quality to use in the egg envelope digestion experiments.
Figure 2 Generation of recombinant milkfish hatching enzymes.
…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The specific caseinolytic activities of the nickel column-purified rMfHE1 and rMfHE3 were 26.8 and 14.2 Δ 280  · min −1  · mg protein −1 , respectively. These values are similar to those of other fish hatching enzymes (30.7 Δ 280  · min −1  · mg protein −1 for ZHE1, 27.3 Δ 280  · min −1  · mg protein −1 for MHCE, and 18.4 Δ 280  · min −1  · mg protein −1 for MLCE) [19]. Thus, we concluded that recombinant enzymes were of sufficient quality to use in the egg envelope digestion experiments.
Figure 2 Generation of recombinant milkfish hatching enzymes.
…”
Section: Resultssupporting
confidence: 84%
“…Seven hatching enzyme cDNAs with 85–95% amino acid identity were cloned from the Japanese eel Anguilla japonica (Elopomorpha) [18]. However, these isozymes were functionally the same in terms of their role in egg envelope digestion [19]. Gene diversification has occurred in the common ancestor of Otocephala and Euteleostei, such that members of these subdivisions possess two types of genes, belonging to two clades, clade I and clade II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of hardening, the fertilized egg envelope becomes insoluble in denaturing reagents, such as urea and SDS. In contrast, the unfertilized egg envelope is generally solubilized by boiling in those reagents, and the component proteins (ZP proteins) dissociate into their monomeric forms (Sano et al., , , ; Yasumasu et al., ). However, the unfertilized Pacific herring egg envelopes did not dissolve completely by boiling in SDS, suggesting that they were partially hardened in the developing oocyte before fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…The liver is one of the largest organs in the body; therefore, it is conceivable that the liver has an advantage in synthesizing a large amount of protein. In fact, the Euteleosts, such as salmon and medaka, also have a thick and tough egg envelope (approximately 30–40 and 20 µm, respectively, Yamagami et al, ), whereas, many elopomorph and otophysian fishes, who synthesize egg envelope proteins exclusively in the ovary, generally have a thin egg envelope (zebrafish, approximately 5 µm; Japanese eel, 1–2 µm; Sano et al, ). Conversely, a possible disadvantage of synthesizing egg envelope proteins in the liver is the transportation cost from the liver to the oocytes.…”
Section: Discussionmentioning
confidence: 99%